PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK DAN MEDIA POWERPOINT DENGAN PEMBELAJARAN HOLISTIK PADA PELAJARAN EKONOMI DI MADRASAH ALIYAH BUKIT HIDAYAH MALINO KECAMATAN TINGGIMONCONG KABUPATEN GOWA - Murniati . (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2017)
The purpose of this study is (1) In order to produce quality learning device IPS Economy class XI-based holistic, namely Learning model Problem Based Learning (PBL) (2) To know the description of learning outcomes IPS Economy class XI using learning tools bebasis holistic, namely Learning model Problem based learning (PBL) (3) To study the response of the learner and teacher responses to the devices and process-based learning is a model of holistic learning Problem based learning (PBL) in social studies in Economics (Accounting). This research is a development (Research and Development) design development using the model of Dick & Carey modified. Subjects were students of class XI Bukit Hidayah Madrasah Aliyah Malino Tinggimoncong Gowa districts. the number of students as many as 28 people. Research data collection is done through questionnaire responses of teachers, the questionnaire responses of learners and learning achievement test and then the data were analyzed using descriptive analysis. The results showed that the developed learning tools that include lesson plans, Powerpoint Media, LKPD and THB after the validation and testing of the device is otherwise in compliance with the validity and can be used in social studies learning Ekonnmi. The results of the analysis of questionnaire responses learner response percentage obtained learners to LKPD of 91.43%, PowerPoint media amounted to 90.54%, and 90.79% Learning Process. These results indicate that the three aspects of getting a very positive response from the learners. While the results of analyzing the response of teachers to RPP 90.00% Media Powerpoint of 92.00%, 92.50% LKPD, categorized as very positive, and the learning process 88.33% with a positive category. Further the study of students have achieved mastery learning classical ie 75.57 with KKM 65. The conclusion is that developed pembelajara device has complied with the validity of the categories of high reliability (1.00) and gained a very positive response from teachers and learners (81-100). Keywords: Holistic Learning, Problem Based Learning Model Learning, Learning Tool